Theoretical and experimental study on convective boiling inside tubes containing twisted-tape inserts - Mogaji, Taye Stephen (2014)
This research comprises an experimental and theoretical study on convective boiling inside tubes containing twisted-tape inserts. The demand for more compact and efficient thermal systems, in which the heat exchangers plays an important role, has led to the development and use of various heat transfer enhancement techniques. Among them twisted-tape insert as a swirl flow device is one of the most used. Twisted-tape inserts have been used for over more than one century ago as a technique of heat transfer enhancement applied to heat exchangers. However, the heat transfer augmentation comes together with pressure drop increment, impacting the pumping power and, consequently, the system efficiency. Moreover, until now it is not clear, the operational conditions under which the heat transfer coefficient augmentation by the use of twisted-tape inserts overcomes pressure drop penalty. In the present study, initially, extensive investigations of the literature concerning convective boiling inside plain tubes with and without twisted-tape inserts were performed. This literature review covers pressure drop, heat transfer coefficient and the leading frictional pressure drop gradient and heat transfer coefficient predictive methods during convective boiling inside tubes with and without twisted-tape inserts. Then, pressure drop and heat transfer coefficient results acquired in the present study were obtained in an experimental apparatus of 12.7 and 15.9 mm ID tubes during flow boiling of R134a for twisted-tape ratios of 3, 4, 9, 14 and tubes without inserts, mass velocities ranging from 75 to 200 kg/m2 s, saturation temperatures of 5 and 15°C and heat fluxes of 5 and 10 kW/m2. The experimental results were parametrically analyzed and compared against the predictive methods from literature. An analysis of the enhancement of the heat transfer coefficient and the pressure drop penalty is presented. Heat transfer coefficient increments up to 45% keeping the same pumping power and pressure drop penalty of about 35% were obtained by using twisted-tape relative to tubes without inserts. Additionally, through comparison of the present study experimental results with the predictive methods from the literature for heat transfer coefficient during two-phase flow inside tube containing twisted-tape inserts, it was verified that non of these methods predict satisfactory well the experimental results. However, a new method was develop for predicting the heat transfer coefficient during flow boiling inside tubes containing twisted-tape inserts based on the experimental results obtained in the present study. The predictive method takes into account the physical picture of the swirl flow phenomenon by including swirl flow effects promoted by the twisted-tape inserts. The proposed method predicts satisfactorily well the data obtained in the present study, predicting 89.1% of the experimental data within an error band of ± 30% and absolute mean deviation of 15.7%.